Association between constipation and risk of stroke: a systematic review and meta-analysis - Tang, Feng; Zhao, Tianjun; Dong, Peiwen; Sun, Kaidi; Sun, Xiaobin; Wang, Qiong (Frontiers in Neurology, 2025)
ObjectiveThis systematic review and meta-analysis aimed to evaluate the association between constipation and stroke risk, with subgroup analyses exploring effects on stroke subtypes.MethodsWe systematically searched PubMed, Web of Science, and Cochrane Library until February 2025. Published studies reporting adjusted odds ratios (ORs), hazard ratios (HRs), or relative risks (RRs) for stroke in constipated versus non-constipated individuals were included. A random-effects model was used to pool effect estimates, with heterogeneity assessed via the chi-square test based on Cochrane Q statistics. Subgroup evaluations were conducted for stroke type (ischemic/hemorrhagic), region, study design, and sex.ResultsThirteen studies involving 684,123 constipation cases and 5,223,378 controls were analyzed. Constipation was associated with a 23% increased stroke risk (pooled OR = 1.23, 95% CI: 1.10–1.36, I2 = 96.51%). Subgroup analyses revealed a stronger association with ischemic stroke (OR = 1.39, 95% CI: 1.19–1.60, I2 = 96.64%) but not hemorrhagic stroke (OR = 1.03, 95% CI: 0.80–1.26, I2 = 78.38%). Notably, constipation showed no stroke risk elevation in women (OR = 1.00, 95% CI: 0.92–1.07, I2 = 0%).ConclusionOur meta-analysis identified constipation as a risk factor for ischemic stroke, but not hemorrhagic stroke. These findings underscore constipation as a modifiable risk factor in ischemic stroke management, warranting further mechanistic and interventional studies.Systematic Review RegistrationPROSPERO 2024; https://www.crd.york.ac.uk/PROSPERO/view/CRD42024615237.